A new species ofRondoniaTravassos, 1920 (Nematoda: Atractidae) parasite ofMetynnis lippincottianus(Cope) (Characiformes: Serrasalmidae) with an amended diagnosis of the genus, based on integrative analyses - Barbosa, Chloe [UNESP]; Ebert, Mariana Bertholdi [UNESP]; Silva, Reinaldo José da [UNESP] (Springer Nature, 2025)
The genus Rondonia Travassos, 1920 comprises nematodes parasitizing teleost fishes and amphibians, but its taxonomic boundaries have long been uncertain due to limited morphological descriptions and lack of molecular data. Here, we provide an integrative taxonomic revision of Rondonia, combining light and scanning electron microscopy with molecular analyses of SSU and LSU rDNA sequences. A new species, Rondonia pardensisn. sp., is described from the intestine of Metynnis lippincottianus (Cope) (Characiformes: Serrasalmidae) in the Pardo River, Paranapanema River basin, Brazil. The new species is distinguished by the presence of a pre-bulbar excretory pore with a protruding teardrop-shaped structure covering it, the number and organization of the cloacal papillae (two pairs pre-cloacal, two pairs ad-cloacal and six pairs post-cloacal), the mouth with three bilobed lips bearing double papillae on each side arranged radially and two amphids, and a larger body size in comparison to its congeners. Phylogenetic analyses confirm its placement within Atractidae and support the monophyly of Rondonia. Based on morphological and molecular evidence, we propose a new taxonomic combination for specimens analysed by Cavalcante et al. (2016), herein reassigned as Rondonia xapuriensisnom. nov. We also examined the type material of Rondonia rondoni deposited by Travassos (1920) using SEM, confirming diagnostic features and recording additional characters that contribute to an updated morphological characterization of the species. In light of these findings, we propose an amended generic diagnosis for Rondonia that reflects its phylogenetic coherence and morphological consistency, and also a key for the identification of the Rondonia species. This study expands the known diversity of the genus, clarifies historical taxonomic uncertainties, and emphasizes the importance of integrative approaches for resolving the systematics of Atractidae.